Advanced group III-nitride nanowire heterostructures - self-assembly and position-controlled growth - Hille, Pascal; Justus Liebig University Giessen (My University, 2017)
Group III-nitride nanowires and nanowire heterostructures were grown by plasma-assisted molecular beam epitaxy. Structural characterization was carried out by electron microscopy and X-Ray diffraction analysis; the optical properties were analyzed by photoluminescence spectroscopy. All samples were grown on GaN nanowire templates fabricated following either the self-assembled or the position-controlled growth approach. The former was performed on Si(111) while a patterned Ti(N) nanohole mask on Si(111) was used for the latter.The self-assembled growth is a well-established method for the fabrication of GaN nanowires on Si(111). So far, the influence of the substrate temperature and metal flux on the properties of GaN nanowires has been intensely discussed in literature. The nitrogen required to form GaN is supplied by an atom source which cracks or excites molecular nitrogen in a RF discharge. In this work, the influence of the operating parameters (nitrogen flux and forward power) of the atom source on the growth and optical properties of GaN nanowires was analyzed. It was shown that an increasing forward power leads to an enhanced formation of point defects, presumably N vacancies. An increasing nitrogen flux seems to increase the density of Ga vacancies close to the nanowire surface.Germanium doping of GaN allows for achieving high free carrier concentrations in homogeneously doped GaN nanowires. This was used to electrostatically screen the internal electric fields in polar GaN nanodiscs embedded between AlN barriers. With increasing carrier concentration, the luminescence signal of the GaN nanodiscs blue shifts and the luminescence lifetimes decrease confirming the screening of the polarization-induced internal electric fields. A reduction of the electric field strength in undoped AlN/GaN nanodisc superlattices was additionally realized by decreasing the AlN barrier thickness. This brings the oppositely charged barrier interfaces closer together, leading to a decrease (increase) of the internal electric field strength in the GaN nanodiscs (AlN barriers). Consequently, a blue shift of the nanodisc luminescence and a decrease of luminescence decay times with decreasing AlN barrier thickness were observed.Furthermore, the influence of the nitrogen flux and the forward power on the growth and properties of In(x)Ga(1-x)N/GaN nanowires were analyzed. Transmission electron microscopy and X-Ray diffraction analysis revealed an inhomogeneous In incorporation. The main luminescence stems from In-rich regions in the nanowires. Increasing nitrogen partial pressure leads to an increasing local In incorporation while no influence of the applied forward power on the In incorporation was observed. However, an increasing forward power during In(x)Ga(1-x)N growth leads to a decreasing luminescence intensity which was assigned to an increasing density of non-radiative recombination centers, presumably due to an increasing density of N vacancies. Carrier confinement similar to that observed in 2D quantum wells was observed in 10x In(x)Ga(1-x)N/GaN nanodisc superlattices. The luminescence signal blue shifts with decreasing nanodisc thickness and bulk-like emission features were identified for nanodiscs exceeding a thickness of 4 nm.The position-controlled growth of GaN nanowires on Ti(N) masks with a hole diameter of 70 nm was developed and optimized. Selectivity of the nanowire growth was demonstrated up to a nanohole pitch of 10 µm which enables single nanowire micro-photoluminescence spectroscopy on as-grown nanowires. Additionally, the growth of In(x)Ga(1-x)N on position-controlled grown GaN nanowires was demonstrated.
Keywords: ddc:530